Pertimbangan Hukum Pergantian Kelamin (Studi Penetapan Pengadilan Negeri Yogyakarta No. 517/ PDT.P/2012/PN. YK dan Penetapan Pengadilan Negeri Boyolali No. 54/PDT.P/2015/Pn.Byl) - Jacqueline Leticia Latifa (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2019)
Indonesia is a legal state. To ensure the continuityof the balance of relations between the citizen, legalrules are needed that aim to create order within thecommunity as stipulated in the Law. Although it hasbeen regulated in the Law, there are still manyviolations carried out by layers of society. Especially ifthere are no legal regulations. Including thephenomenon of transsexual. Along with thedevelopment of technology and the times, many peoplecarrying out sex reassignment operations for the sakeof health or just follow the trend causing pro and contraamong the community in responding to transsexual dueto the absence of laws specifically regulating whetheror not totranssexual. However, even though there is alegal vacuum, based on Article 10 paragraph (1) of LawNumber 48 Year 2009 concerning Judicial Power, thejudge may not reject the case that goes to court. So,how do judges use the law in considering theirdecisions?This type of research is library research bymaking library materials as the main data source. Thetheoretical framework used is the theory of judges'consideration which includes the theory of legalcertainty, the theory of justice, and the theory ofexpediency. While the approach theory used isnormative juridical, namely the method used in legalresearch conducted by examining existing librarymaterials.The results of this study indicate thatalthough there are no specific legal rules regardingtranssexual, the judge must be able to explore, follow, and understand legal values. Yogyakarta District Courtjudges in granting transsexual requests only considerpositive law, while Boyolali District Court judges ingranting transsexual requests not only consider positivelaw but also use Islamic law and MUI fatwa’s. In thecontext of Maslahah, both Yogyakarta District Courtjudges and Boyolali District Court judges, bothconsidered problems or benefits for applicants totranssexual. As for the transsexual request in the courtit turned out to be requested after the sex operationwas carried out so that the function of the court wasonly as a formal legality towards the practice oftranssexual. Supposedly if the law has a function as anengineering so that the behavior of citizens is orderlyand in accordance with the value of health, then thefunction of the court can assess whether thetranssexual is legally acceptable or not.